Gender, Willingness to Compete and Career Choices Along the Whole Ability Distribution - Thomas Buser; Noemi Peter; Stefan Wolter (Tinbergen Institute, 2017)
Men are generally found to be more willing to compete than women and there is growing evidence that willingness to compete is a predictor of individual and gender differences in career decisions and labor market outcomes. However, most existing evidence comes from the top of the education and talent distribution. In this study, we use incentivized choices from more than 1500 Swiss lower-secondary school students to ask how the gender gap in willingness to compete varies with ability and how willingness to compete predicts career choices along the whole ability distribution. Our main results are: 1. The gender gap in willingness to compete is essentially zero among the lowest-ability students, but increases steadily with ability and reaches 30-40 percentage points for the highest-ability students. 2. Willingness to compete predicts career choices along the whole ability distribution. At the top of the ability distribution, students who compete are more likely to choose a math or science-related academic specialization and girls who compete are more likely to choose academic over vocational education in general. At the middle, competitive boys are more likely to choose a business-oriented apprenticeship, while competitive girls are more likely to choose a math-intensive apprenticeship or an academic education. At the bottom, students who compete are more likely to succeed in securing an apprenticeship position. We also discuss how our findings relate to persistent gender differences in career outcomes.
Keywords: D91; J16; J24; 330; willingness to compete; gender; career decisions